Beef quality labels: A combination of sensory acceptance test, stated willingness to pay, and choice-based conjoint analysis. (1st August 2018) - Meyerding, Stephan G.H.; Gentz, Maria; Altmann, Brianne; Meier-Dinkel, Lisa
Abstract: Consumer perspectives of beef quality are complex, leading to a market that is increasingly differentiating. Thus, ongoing monitoring and assessment of changes in consumer perspectives is essential to identify changing market conditions. Often only credence and search characteristics are evaluated in consumer studies; therefore the object of the present study is to examine consumer preferences and perceptions towards beef steaks, also including experience characteristics, using a mixed methods approach. For this reason, 55 consumers participated in an experiment in Germany, including a sensory acceptance test, stated willingness to pay, and choice-based conjoint analysis (CBCA). Different quality characteristics were included, but a focus on the quality labels of 'dry aged beef', 'Block House beef', and 'Angus beef' was predominant throughout the experiment with the results showing that quality labels significantly increased overall liking as well as the stated willingness to pay. Quality labels were also the one of the most important characteristics in the conjoint analysis, after origin and price. The results of all applied methods are comparable for the characteristic quality label. The combination of sensory acceptance test and CBCA were additionally able to evaluate all three kinds of beef quality characteristics, which could not be evaluated together only using a single method. This suggests that a mixture of methods should be used to gain better knowledge on the true behavior of beef consumers. Experience and credence characteristics, including beef quality labels, present opportunities for future research as well as the potential for determining product and market differentiation.